Microscopic mechanism analysis of influence of high effective confining pressure on mechanical properties of hydrate-bearing sediments. (December 2022) - Xu, Jialin; Xu, Chengshun; Wang, Rui; Jiang, Chenglong; Jiao, Shuang; Hyodo, Masayuki
Abstract: It was discovered in tests that the increase in effective confining pressure could have a great impact on the mechanical behavior of hydrate-bearing sediment, which was not only decreased the internal friction angle and dilatancy, but also enhanced cohesion and strength. Significant crushing of the hydrate-host sand was founded after shearing under high pressure. In this study, a discrete element method (DEM) model considering the effects of particle breakage and hydrate repolymerization was proposed, and a series of numerical triaxial tests were performed to shed light on the mechanism of mechanical properties evolution observed in the physical tests. The numerical results revealed that the breakage of host particles was a leading cause of the decrease in the internal friction angle and transformation from shear dilation to contraction. As the hydrate saturation, axial strain, and effective confining pressure increased, the force chain network of the model became denser and the force magnitude on the chains became increasingly uniform, which leads to the increase in model strength; the number and force of bonded contact also increased gradually, resulting in increased cohesion on the macro scale.